Fast algorithm for calculating the pressure pulsation in a reciprocating compressor system with stepless capacity regulation. (December 2019) - Yang, Lanlan; Jia, Xiaohan; Qi, Haojie; Feng, Jianmei; Peng, Xueyuan; Wang, Zhizhong
Stepless capacity regulation through delayed closure of suction valves plays an important role in energy conservation for reciprocating compressors. Serious gas pulsation usually occurs with a suction valve unloader, and its analysis and suppression is a challenge owing to the varied components of the pulsation excitation under different conditions. In this study, a fast algorithm was proposed to calculate the gas pulsation of a compressor system with stepless capacity regulation and was further incorporated into the frequency-domain modeling of the gas pulsation. A test rig was constructed, and the model was experimentally verified. The dynamic pressure at positions in the suction and discharge valve chambers was measured, as the compressor capacity was varied by changing the closing time of the suction valves. The experimental data were compared with the simulated results and indicated a good agreement. The results showed that the suction valve unloader had a negative impact on the gas pulsation in the suction pipeline system. The pressure pulsation of the main excitation frequency increased in the suction pipeline system and decreased in the discharge pipeline, as the opening time of the suction valve increased.